An ecological study of a chionochloa population : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science at Massey University of Manawatu - McPherson, Hugh Grant (Massey University, 1966)
The Chionochloa community under study occupies approximately 63 acres on the summit of Mt Kaiparoro (2,660 ft a.s.l.), a large ridge situated about four miles east of the main northern Tararua Range and separated from it by the headwaters of the Mangatainoka River (fig. 1). The crest of this ridge slopes upwards towards the summit at the southern end, rising 200 feet over the length of the tussock grassland clearing. The clearing extends only a short distance down the sides of the ridge. On all but the northern edge the transition zone from grassland through scrubland to forest occurs where there is a marked increase in slope (fig. 2). The area covered by tussock grassland is gently undulating, but small streams dissect the area at irregular intervals, causing considerable local variation in slope. [From Preface]
Keywords: Tararua Range New Zealand; Botany; Ecology; Grasses